PENANGANAN PASCA PANEN BUAH-BUAHAN DAN SAYURAN - -, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2007)
ABSTRACT Horticulture is the designation of category plant fruits, vegetables and ornamental plants. As Characteristics of horticultural products the plant fruits and vegetables are perishable products that need a proper post-harvest handling. Post harvest handling is needed to maintain the quality of the results so that when consumed gisinya value does not go down, but farmers in Indonesia have not been able to do post-harvest handling of fruits and vegetables correctly, due to the limitations they. Variety of ways post-harvest handling of fruits and vegetables is a beginning of cooling (recooling), sorting, washing, fumigation, packaging and storage. Key word : post harverst fruits and vegetables